Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø·Ø±ÙŠÙ‚Ø© ØÙ„ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ù„ØªØ±Ù‚ÙŠØ© Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø¨Ø© Ø¹Ù„Ù‰ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© (Ø§Ù„Ø¨ØØ« Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ Ø¨Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø¹Ù„ÙˆÙ… Ø§Ù„Ø¹ØµØ±ÙŠ Ø¨Ø¨Ù†Ø¯Ø§ Ø£ØªØ´ÙŠÙ‡) - razi, Fachrur ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2020)
Reading is the third language skill of the four main skills, namely Listening, Speaking, Reading and Writing skills. The Qiraatul Kutub is one of lessons though for fourth and fifth grade students (first and second year of high school) at Dayah Modern Darul â€˜Ulum Banda Aceh. And the researcher intends to research about the ØÙ„ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª method and effects of its application to the teaching of Qiraatul Kutubâ€™s lesson to students in this school, so that the researchers can find out that this method is effective or not effective to the teaching of Qiraatul Kutubâ€™s lessons. This study used a quasi-experimental method. Researchers took samples 50 students, namely 25 students of class 5-a as the experimental group and 25 students of class 5-b as the control group. And the researchâ€™s instrument is Interview, Observation and Test (pre test-post test). The study results showed that The use of the ØÙ„ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª method is effective for students in learning of Qiraatul Kutubâ€™s lesson. It was shown by the result of the t-test = 4,2 is greater than 2,021 results (0,05).